2001
DOI: 10.1248/cpb.49.1662
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Capsanthin Using Lewis Acid-Promoted Regio- and Stereoselective Rearrangement of Tetrasubstituted Epoxide.

Abstract: The synthesis of capsanthin 1 was accomplished via the C 15 -cyclopentyl ketone 13 prepared by Lewis acid-promoted regioand stereoselective rearrangement of the epoxide 12.Key words capsanthin; tetrasubstituted epoxide; regio-and stereoselective rearrangement; total synthesis Previously, we reported 1) the first biomimetic type total synthesis of both crassostreaxanthin B 2 (Fig. 1) possessing a novel acyclic-tetrasubstituted olefinic end group and mytiloxanthin 3 containing a cyclopentyl enolic b-diketone gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…HPLC analysis using a chiral column (CHIRALPAK AY-H; Daicel) revealed that the enantiomeric excess (ee) of the cyclopentyl ketone 6a (84% ee) remained almost unchanged during the rearrangement of C 15 -epoxy dienal 5a (94% ee). From the previous results, 8,9) the absolute stereochemistry of the newly formed C-5 chiral center in rearrangement product 6a was expected to be (R); however, its configuration was determined by an alternative synthesis from (ϩ)-(R)-camphonanic acid (11) 13) (Chart 2). Esterification of the acid 11 with TMSCHN 2 14) followed by reduction with LiAlH 4 gave the corresponding alcohol 12 15) (88%).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…HPLC analysis using a chiral column (CHIRALPAK AY-H; Daicel) revealed that the enantiomeric excess (ee) of the cyclopentyl ketone 6a (84% ee) remained almost unchanged during the rearrangement of C 15 -epoxy dienal 5a (94% ee). From the previous results, 8,9) the absolute stereochemistry of the newly formed C-5 chiral center in rearrangement product 6a was expected to be (R); however, its configuration was determined by an alternative synthesis from (ϩ)-(R)-camphonanic acid (11) 13) (Chart 2). Esterification of the acid 11 with TMSCHN 2 14) followed by reduction with LiAlH 4 gave the corresponding alcohol 12 15) (88%).…”
Section: Resultsmentioning
confidence: 97%
“…3-Deoxycapsanthin (1) To a solution of the phosphonium salt 20 8,9) (1.14 g, 2.0 mmol) and the all-E apocarotenal 17 (83 mg, 0.23 mmol) in MeOH (15 ml) was added NaOMe (1.0 M in MeOH; 3.0 ml, 3.0 mmol) at rt. After being stirred at rt for 3.5 h, Dowex 50 W-X8 (H ϩ ) (5 g) was added to the reaction mixture and this was stirred at rt for 5 min.…”
Section: Preparation Of the Wittig Salt (24)mentioning
confidence: 99%
See 2 more Smart Citations
“…From the previous results 4) in the reaction of epoxides 3a-e with an olefinic group at C-6 5) (Chart 2) with Lewis acid, we found that the direction of the oxirane ring cleavage depended upon both the length of conjugated double bond system and the electron-withdrawing ability of the substituents adjacent to the double bond. Epoxides 3a and 3d carrying a strong electron-withdrawing group (EWG) predominantly provided the cyclopentyl ketones 5a and 5d, respectively, via cleavage of the oxirane ring at the C-5 position (route b), whereas 5,6-epoxides 3b, 3c, and 3e only gave 5,8-epoxides 4b, 4c, and 4e, respectively, via opening of the C-6-oxygen bond of the oxirane ring (route a).…”
mentioning
confidence: 73%